PENERAPAN METODE USER CENTERED DESIGN PADA USER INTERFACE & USER EXPERIENCE SISTEM ONLINE BOOKING SERVICE BERBASIS WEBSITE DI CV SALUYU MANDIRI PRATAMA - Ali, Mohammad Khaidir; Rohmanu, Ajar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Today's technological developments encourage many companies to try to make it easier for the needs and convenience of online transactions, one of which is introducing a website-based booking service system and spare parts store. However, there are still challenges in designing optimal user interfaces and user experiences to achieve the company's business goals. This study aims to apply the User Centered Design (UCD) method to the appearance of an online booking service system and website-based spare parts shop at CV Saluyu Mandiri Pratama. User Centered Design (UCD) is an approach that focuses on the user in the entire manufacturing process, starting from user understanding, requirements gathering, prototyping, to user evaluation. The research methodology includes the stages of analyzing user needs and user context, creating interface concepts, developing prototypes, and evaluating users. Analysis of user needs is carried out through interviews, observation, and literature studies to understand user needs and preferences. Prototype development is carried out using interface creation tools that allow users to visually interact with the system. The results of this study are applications that pay attention to user needs and preferences, and provide optimal user experience. The User Centered Design (UCD) method has proven to be effective in assisting companies in designing systems that are more relevant and satisfying to users.